Analisis Kebutuhan Pengembangan Media Pembelajaran Sejarah Komik Digital - Rizka Putri; Ridho Bayu Yefterson (Jurusan Sejarah FIS UNP, 2022)
Learning media is one of the supporting components that teachers should not miss in an effort to achieve learning success. In history learning which has a lot of learning materials, teachers often prefer teacher-oriented teaching methods. Because the teacher's teaching method is teacher oriented, it has an impact on students, namely students become more passive in learning and cannot achieve learning objectives. So we need media that can be a solution to these problems, one of which is comic media. The purpose of this study was to analyze the need for comics media as learning media in Indonesian history subjects. This research is a qualitative research. This research was conducted by analyzing problems and causes of problems and analyzing curriculum needs, student needs, teacher needs and material needs. It was concluded that as many as 20 students were interested in digital comic media and the other 10 answered neutrally.